DAVID: A disease and vector integrated database - Robinson, Timothy P. (European Union, 2001)
The Disease and Vector Integrated Database (DAVID) is a geographical information system for managing field data on tsetse, trypanosomiasis and livestock. It is used to enter these data in a computer to verify and query the data and to produce output Reports in the form of tables, graphs and maps. A key feature of the database is that all data are temporally and geographically registered, enabling data from tsetse, trypanosomiasis and livestock surveys to be integrated. For a particular country the programme is customised by providing administrative overlays; national veterinary area overlays; lists of livestock inspection sites; lists of diagnostic methods used; lists of tsetse sampling sites; lists of tsetse sampling methods used; and lists of tsetse and trypanosome species present. This paper discusses the database design; data entry and verification; and output. Examples of graphic output from the DAVID programe are presented.